2021
DOI: 10.1155/2021/6620294
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Weathered Petroleum Hydrocarbons Using Organic Waste Amendments

Abstract: Extraction, transport, and processing of petroleum products have resulted in inadvertent contamination of soil. Various technologies have been proposed for removal of petroleum hydrocarbon contaminants, including biological techniques. Treatment of aged (weathered) petroleum compounds is challenging, as these wastes tend to be enriched with recalcitrant hydrocarbons. The purpose of the reported study was to investigate remediation of weathered petroleum via simulated landfarming using selected soil amendments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Active carbon can also eliminate the side effects of volatile and nonvolatile organic pollutions, even at high levels of concentration. Activated carbon limits the evaporation and leaching loss of TPHs due to their rapid and irreversible immobilization, which increase the availability of contaminants for biodegradation (Yousefi et al 2021). In the study of the biodegradation of petroleum hydrocarbons using organic adsorbents, Yousefi et al (2021) reported that activated carbon removed 74% of petroleum hydrocarbons over 15 weeks.…”
Section: Concentration Of Tph In the Polluted Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…Active carbon can also eliminate the side effects of volatile and nonvolatile organic pollutions, even at high levels of concentration. Activated carbon limits the evaporation and leaching loss of TPHs due to their rapid and irreversible immobilization, which increase the availability of contaminants for biodegradation (Yousefi et al 2021). In the study of the biodegradation of petroleum hydrocarbons using organic adsorbents, Yousefi et al (2021) reported that activated carbon removed 74% of petroleum hydrocarbons over 15 weeks.…”
Section: Concentration Of Tph In the Polluted Soilmentioning
confidence: 99%
“…Moreover, the highest TPH biodegradation rate constant (0.0419 day −1 ) and lowest half-life (16.54 days) were observed in biostimulants + bioaugmentation treatment, which suggests that this treatment had the highest efficiency for TPH removal. Yousefi et al (2021) investigated the effect of plant compost, paper mill sludge, molasses and active carbon on petroleum degradation in the polluted soil collected from Sarvestan and Saadat abad oil field located in the south of Zagros, Iran, over 15 weeks. The results showed that TPH biodegradation kinetics was of first order, and degradation rate constant in molasses, paper mill sludge, plant compost and active carbon was 0.005, 0.004, 0.003 and 0.002 day −1 , with 71, 93, 107 and 139 days half-life, respectively.…”
Section: Biological Degradation Kinetics and Tph Half-lifementioning
confidence: 99%
“…As the hydrocarbon contaminant is highly persistent with some toxicity packages, this can have long-term effects on many cold temperate species and further destroy the ecosystem. Thus, oil spills have created a great need for remediation efforts to be considered [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%